An input‐output mathematical model for measuring the productivity of road‐transport companies - Oke, Sunday A. (Transport, 2005)
This paper presents a mathematical model for measuring the productivity of a transport company that is engaged in commercial transport activities. The model is input‐output based and takes into account the inflation factor that the system resources are subjected due to the changes in prices of these input items. Drawing from the principles of composite variable formulation in differential calculus, the productivity framework was formulated to mimic Maclaurin series function in mathematical sciences. Based on this boundary conditions were set in order to have a definite model that measures the productivity of the transport system. A hypothetical case study was formulated and solved to demonstrate the practical applicability of the model proposed. Arising from this there is a number of graphical presentations of the results that validate the feasibility of measuring the productivity of the transport company using the model developed. First Published Online: 27 Oct 2010